Thirty Years of Conflict and Economic Growth in Turkey: A Synthetic Control Approach - Fırat Bilgel; Burhan Can Karahasan (London School of Economics and Political Science (LSE), European Institute, 2016)
This study seeks to estimate the economic effects of PKK terrorism in Turkey in a causal framework. We create a synthetic control group that reproduces the Turkish real per capita Gross Domestic Product (GDP) before PKK terrorism emerged in the second half of the 1980s. We compare the GDP of the synthetic Turkey without terrorism to the actual Turkey with terrorism for the period 1955-2008. Covering the period of 1988-2008, we find that the Turkish per capita GDP would have been higher by an average of about 1,585 per year had it not been exposed to PKK terrorism. This translates into an average of 13.8 percent higher per capita GDP or a 0.62 percentage points higher annual growth over a period of 21 years. Our estimate is robust to country exclusion, sparse controls, various non-outcome characteristics as predictors of GDP, alternative specifications of the in-space placebo experiments and to other potentially confounding interventions to the sample units in the pre-terrorism period.
Keywords: C15; D74; P59; 330; separatist terrorism; synthetic control; Turkey; economic development; causal inference